Analysis of Inverter Operation Modes of an IGBT-Based ZCS LLC Converter for a 2 kW Automotive On-Board DC-DC - Urbaneck, Daniel; Wiegard, Jan; Schafmeister, Frank (PCIM Europe 2024; IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)

Pitfalls and their Avoidability in the Double-Pulse Test - Förster, Nikolas; Urbaneck, Daniel; Kohlhepp, Benedikt; Kübrich, Daniel; Schafmeister, Frank (PCIM Europe 2024; IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)

Advanced Synchronous Rectification for an IGBT-Based ZCS LLC Converter with High Output Currents for a 2 kW Automotive DC-DC Stage - Urbaneck, Daniel; Böcker, Joachim; Schafmeister, Frank (PCIM Europe 2023; IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)

Advanced Synchronous Rectification for an IGBT-Based ZCS LLC Converter with High Output Currents for a 2 kW Automotive DC-DC Stage - Urbaneck, Daniel; Schafmeister, Frank; Böcker, Joachim (PCIM Europe 2023)
State-of-the-art LLC resonant converters use MOSFETs in their inverter stage, which allows high switching frequencies and thus the use of compact magnetic components. The large parasitic output capacitance and the poor reverse-recovery behaviour of the inherent body diode of high-voltage (600 V) silicon MOSFETs require soft switching, i.e. zero-voltage switching (ZVS). Otherwise, the high turn-on switching losses would lead to excessive heating and ultimately to the destruction of the switch. Therefore, MOSFET-based LLC converters are operated in the so-called inductive region only, which enables ZVS. The use of robust and cost-effective IGBTs instead of MOSFETs is particularly advantageous for automotive applications, since in addition to high reliability low costs are an important objective here. Since IGBTs are characterized by dominant turn-off losses and generally higher switching losses compared to MOSFETs, the aim is to operate them with zero-current switching (ZCS) and at low switching frequencies below the resonance frequency. In this region also the voltage transfer characteristic is steeper, which qualifies for applications with a strongly varying input-to-output voltage ratio, such as given for automotive on-board DC-DC converters connecting the (high-voltage) traction battery with the (12 V) auxiliary battery. In this paper, a stress value analysis based on a switched-model simulation is used to design a ZCS LLC converter and take advantage of the mentioned benefits of IGBTs as well as of the steeper voltage transfer characteristic. Within this operation region below the resonance frequency, however, a new phenomenon of several current pulses occurring during a single switching period through the rectifier components may appear. Generally, in applications with high output currents a synchronous rectifier (SR) is often used to keep the conduction losses of the rectifier stage at a moderate level: Low-voltage MOSFETs, which actively need to be gated synchronously to the polarity of the current pulses, are employed then instead of more lossy rectifier diodes. However, standard SR driver ICs have been shown to be unable to properly rectify the multi-pulse output currents of the proposed LLC operation, resulting in high conduction losses of the rectifier stage. A cost-effective hardware concept is presented which ensures proper rectification by using standard SR-ICs that are actively overdriven by the converter’s central microcontroller. A 2 kW prototype for an EV on-board DC-DC converter was built to show the effectiveness of the method, documenting an increase in efficiency by up to 4.1 % compared to a purely SR-IC-based solution. Overall efficiency is very similar to that of a conventional (MOSFET-based) LLC converter so that the ZCS-operated LLC IGBT-converter represents a cost-effective alternative, which even shows 10 % less worst-case losses.
Keywords: LLC Converter; IGBT; ZCS; Synchronous Rectification

LLC Converter in Capacitive Operation Utilizing ZCS for IGBTs – Theory, Concept and Verification of a 2 kW DC-DC Converter for EVs - Urbaneck, Daniel; Rehlaender, Philipp; Böcker, Joachim; Schafmeister, Frank (2021 IEEE Applied Power Electronics Conference and Exposition (APEC))
LLC resonant converters typically employ power MOSFETs in their inverter stage. The generally weak reverse recovery behaviour of the intrinsic body diodes of those MOSFETs causes significant turn-on losses when being forced to hard commutations. Continuous operation in this way will lead to self-destruction of the transistors. Consequently, zero-voltage switching (ZVS) is essential in a MOSFET-based inverter stage. To ensure ZVS, the LLC converter is operated in the inductive region. On the contrary, IGBTs show dominant turn-off losses and are therefore conventionally not applied in LLC converters typically requiring high switching frequencies to achieve low output voltages. However, if the LLC converter is intentionally designed for capacitive operation, zero-current switching (ZCS) is enabled and thus robust and cost-efficient IGBTs can be applied in the inverter stage. The aim of this work is to investigate the use IGBTs in the inverter of an LLC converter. The theory behind the capacitive operated LLC is derived using a switched simulation model and compared with the fundamental harmonic approximation (FHA). The results prove FHA to be useless for practical converter design. Instead, a stress value analysis based on switched model simulations is proposed to the design a capacitive operated LLC utilizing ZCS. A 2 kW prototype for on-board EV applications was built to verify the theory and design approach. The prototype confirms the derived theory and thus the deployment of IGBTs in the inverter stage of LLC resonant converters. Synchronous rectification turns out to require a specific control solution, but if given the resulting efficiency in the most critical operation point exceeds the value of a MOSFET-based (inductive operated) LLC-design of an identical application. Therefore, this concept should be further developed.

LLC Converter Design in Capacitive Operation utilizes ZCS for IGBTs – a Concept Study for a 2.2 kW Automotive DC-DC Stage - Urbaneck, Daniel; Rehlaender, Philipp; Schafmeister, Frank; Böcker, Joachim (PCIM Europe digital days 2020)
LLC resonant converters generally employ MOSFETs in the inverter stage, which can be of half-bridge (HB) or full-bridge (FB) type. The generally weak intrinsic (body) diodes of the MOSFETs cause turn-on losses when being forced to hard current commutations finally leading to the components self-destruction when operated constantly in this way. Consequently, zero-voltage switching (ZVS) operation is more or less essential in a silicon (Si) MOSFET-based HB or FB. To ensure ZVS, the LLC is operated in the inductive region, i.e. with lagging resonant current. On the contrary, IGBTs show dominant turn-off losses and therefore are conventionally not applied in LLCs typically requiring high switching frequencies to achieve low output voltages. Yet, if the LLC is intentionally designed for the capacitive region, i. e. operation with leading current, zero-current switching (ZCS) enabling IGBTs in the inverter stage can be ensured. This paper explores in detail the LLC in the capacitive operating region and gives design considerations for a capacitive LLC utilizing both robust and cost-efficient IGBTs for an exemplary 2.2 kW automotive on-board DC-DC converter application. The results of a loss analysis show that the LLC resonant converter can be operated well in the capacitive region. In the given case, significantly lower overall and 30 % lower inverter stage losses are achieved in the thermally relevant worst-case comparison with an inductive LLC based on Si MOSFETs.